Contribution of adapted physical activity on body composition and fitness related to the health of vascular hemiplegic patients - Bofosa, Teddy; Kam, Eric; Miangindula, Betty (Journal of Surgery and Medicine, 2019)
Aim: Stroke is a neurological deficit of vascular origin lasting more than 24 hours. We aimed to examine the impact of the functional rehabilitation associated with the practice of adapted physical activities on body composition and fitness related to the health of vascular hemiplegic patients. Methods: We chose the case-control study method which is consisted to evaluate the body composition and health-related fitness of 90 male hemiplegic patients, after randomization, 40 of whom were in the experimental group undergoing a functional rehabilitation program associated with the practice of adapted physical activities and 50 of the control group submitted to a functional rehabilitation program. Results: After the two intervention programs we found that subjects in the experimental group significantly changed total fat, visceral fat and muscle compared to the control group (P<0.001, P=0.004 and P=0.029, respectively). Their resting heart rate, respiratory rate, muscle strength, walking speed and rate were significantly reduced compared to the control group (P<0.001 for all mentioned comparisons). In addition, their resting systolic blood pressure, resting diastolic blood pressure, forced expiratory volume, muscle strength and Motor skills were significantly improved compared to the control group (P=0.048, P=0.027, P=0.003, P=0.015 and P=0.003, respectively). Conclusion: This study shows that the functional rehabilitation program associated with the regular practice of adapted physical activities is more beneficial in improving the morphological state and fitness of hemiplegic patients than the isolated use of functional rehabilitation.